Estudos sobre a especificidade de antígenos e sua aplicabilidade para o imunodiagnóstico das angiostronilíases - Cognato, Bianca Barbieri (2017)
Two nematode species belonging to the Metastrongyloidea superfamily are capable to produce disease in humans: Angiostrongylus cantonensis and Angiostrongylus costaricensis. Both are rodent parasites and human infection is considered accidental. Eosinophilic meningoencephalitis, caused by A. cantonensis, raises concern due to the expanding number of cases and geographical area of occurrence. Molecular and immunological methods for the diagnosis are crucial, however, after many studies with different antigenic molecules, has a specific and sensitive test to discriminate the angiostrongyliasis to others parasitoses is lacking. Cross-reactivity with other helminthes, which may cause similar symptoms, and eosinophilic meningitis, has been a problem for the satisfactory performance of specificity in serological tests. In order to improve the diagnosis of angiostrongyliasis, a comparative analysis of protein recognition from different extracts from A. cantonensis, Toxocara canis, Schistosoma mansoni and Strongyloides stercoralis against positive serum for Angiostrongylus.spp was performed. Through extraction kit, one-dimensional and two-dimensional electrophoresis, western blot and mass spectrometry, 149 proteins were identified. Among these, 34 were exclusive to A. cantonensis, COI being present only in the A. cantonensis extract, having no similarities with any other parasite compared in NCBI (nr database) and WormBase Database. Additionally, nine proteins were recognized by more than one parasite and extract, being important cross reactivity markers in parasitic infections. With the data obtained in this study, we suggest the use of the follow proteins as cross-reactivity markers: Galectin 1, HSPA-5 and Ifa1. In addition, immunogenic proteins of A. cantonensis ES-7, Lec-5 and 14-3-3, were recombinant expressed in two cell types, CHO and HEK. Their potential diagnostic values were verified by uni and bidimensional electrophoresis, western and dot blot, and N-glycosidase F (PNGase F) treatment using serum from patients infected with A. cantonensis, negative serum for parasites, and positive for other parasites. ES7 protein expressed in HEK and CHO cells and Lec-5 expressed in CHO were recognized only by Angiostrongylus-positive serum and not by negative control and specificity control in 2D and 1D tests, respectively. In the 2D analyzes Lec-5 showed a weak recognition with negative serum. However, the 14-3-3 protein didn´t show any specificity against A. cantonensis serum, since it was recognized by all tested sera. Antigen-antibody recognition was found to be dependent on the glycogenic portions, since when treated with N-glycosidase F (PNGase F), recognition between proteins and serum disappeared. The heterologous expression, using mammalian cells, as well as the identification of shared and/or specific molecules, may represent a promising source of antigens for the diagnosis of eosinophilic meningoencephalitis, and molecular diagnostic tests become necessary.